Mohammed Nabiyude jeevitha santhesam - Hameed, M. Shahul (Trivandrum, 1987)
One of the most important books in the series of important books published by the Department of Inquiry is the biographical series 'Keraliya Mahatmas' which includes all the memorable cultural figures of Kerala including spiritual gurus, thinkers, writers, rulers, movement leaders and social transformation heroes. But in contrast, we have given special consideration to the publication of the book 'Message of the Life of the Prophet Muhammad'. Born and raised in Arabia, Saudi Arabia, we have undertaken the publication of this book as a biography of a world-renowned Mahatma. The author, Shri. M. Shahul Hameed, Dr. A. who checked the book and paid the fines. N. P. Rev. Ummerkutty Prof. O. Ayyaneth, Dr. M. Lilavati would also like to take this opportunity to express our gratitude to the Department of Cultural Publications. We would also like to take this opportunity to express our gratitude to the members of the Advisory Council who assisted us from time to time in giving valuable suggestions for the publication of this book.
Keywords: "Nabiyude, Mohammed"